USING ART AND CRAFTS TO TEACH ENGLISH TO YOUNG CHILDREN - Baratova, Khadjimuratova, Umida, Ugiloy (Журнал иностранных языков и лингвистики, 2021)
Majority of young leaners feel anxiety when it comes to language learning and especially grammar rules. The article discusses the ways of teaching children in anxiety free environments and using arts and crafts as a solution to this problem.